Mediating Factor of Strategy Business in the Relationship between Environmental and Business Performance - Prasetio Ari Wibowo; Juhary Ali; Johan Budiman (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
The purpose of this study is to examine the impact of the internal and external business environment on the formulation of business strategy, the impact of business strategy on business performance, and the impact of the internal and external business environment on the performance of the Service and Creative Industry Cluster MSMEs in DKI Jakarta. This study employs a quantitative approach to research, collecting data through observation and interviews and processing primary data derived from respondents' questionnaire responses. Using SEM-PLS 3 Version, the validity test, the reliability test, outer loading, the inner model fit (R-Square), the significance test (hypothesis test), and the F-Square Test are then utilized to assess the study data. F-square of 0.409 > f-square of 0.35, the External Environment has a moderate influence on Business Strategy. The moderate influence of the Internal Environment on the Outcome of Small and Medium-Sized Enterprises, as indicated by the F-Square value of 0.29, is accompanied by a modest effect. The finding from this research indicates that the service and creative industry cluster MSME actors in DKI Jakarta formulate business strategies to become Prospector, Analysts, Low-Cost Defender, and Different Defender based on or have different external environmental backgrounds in terms of demography, politics/law, economic conditions, and the technology used to run their respective businesses.